Pengaruh Ekspor Migas dan Non Migas terhadap Pertumbuhan Ekonomi Aceh - Moana Afliana (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Aceh’s economy has long been dominated by the oil and gas sector, particularly LNG Arun exports, which contributed more than 40% of regional GDP (GRDP) in the early observation period. However, declining production after 2014 drastically reduced its share to below 20%, and in recent years, to only around 10–12%. This study aims to analyze the contribution of oil and gas (migas) and non-oil and gas (nonmigas) exports to Aceh’s economy and to assess the potential of export diversification as a sustainable development strategy. The research employs a quantitative approach using secondary time series data from 2007–2021 obtained from BPS, Bank Indonesia, and other official sources. Data were analyzed descriptively and through simple econometric models, including OLS regression and cointegration tests. The findings reveal that oil and gas exports are significant in the short term but have weakened in the long term. In contrast, non-oil and gas exports, although relatively small, exhibit stable growth and demonstrate a long-term relationship with GRDP. These results underscore the importance of diversifying exports towards nonmigas commodities, particularly coffee, cocoa, rubber, and fisheries. The practical implication is the urgent need for Aceh’s development strategy to shift from oil and gas dependence towards globally competitive nonmigas industrialization